Telling stories: a critical examination of the works of Tracy Emin (b. 1963) and Claudette Schreuders (b. 1973). - Hossack, Daryl Fran (My University, 2008)
Abstract This research paper examines the ways in which the autobiographical impulse is constructed in selected artworks of Tracey Emin (b1963-) and Claudette Schreuders (b1973-). It is situated within contemporary discourses around notions of the self, namely postmodernist, feminist and post colonialist frameworks. This critical discussion of notions of the self, as evidenced in these selected artworks, leads into discourses of Authenticity, of Histories, personal and collective and of the role Identity formation plays in the performing self. In conducting this research I have drawn on a wide range of theoretical frameworks including philosophy, psychoanalysis and literary theory, including magical realism. The first part of my study presents the theoretical frameworks of Authenticity, History and Identity regarding the autobiographical impulse. The second section of this paper examines the selected works of Emin and Schreuders. I chose these two artists because of their different strategies in performing themselves rather than their similarities, which allows for an interrogation of a broader framework of contemporary artistic practices. The concluding chapter examines my practical artwork during the period of my Masters degree. My work comes from an autobiographical base and I create a ‘self-portrait’ through my accumulation, production and display of objects. My exhibition took the form of an installation whereby I created an uncomfortable atmosphere through various methods including stimulating the olfactory sense in a predominant way.
Keywords: autobiography in visual art; identity